Dolphin Tale - Smith, Charles Martin; Connick, Harry, Jr., 1967-; Judd, Ashley; Gamble, Nathan (Burbank, CA : Warner Home Video, 2012)
Eleven-year-old Sawyer Nelson becomes fascinated by the efforts of a local aquarium to save a dolphin injured in a crab trap.
Camera, Karl Walter Lindenlaub ; editor, Harvey Rosenstock ; music, Mark Isham.
Harry Connick, Jr., Ashley Judd, Nathan Gamble, Kris Kristofferson, Cozi Zuehisdorff, Morgan Freeman, Austin Stowell.
MPAA rating: PG.
DVD.
Keywords: Dolphins -- Drama; Wildlife rescue -- Drama; Public marine aquariums -- Florida -- Drama; Animal films; Fiction films; Feature films